KEMAMPUAN MEMPRODUKSI TEKS EKSPOSISI SISWA SEKOLAH MENENGAH ATAS DI KOTA MATARAM DITINJAU DARI ASPEK STRUKTUR TEKS EKSPOSISI - Nur Ida Rosmayanti; Mahsun Mahsun; Johan Mahyudi (JURNAL SKRIPTA, 2021)
This study aims to describe the ability to produce Non-Literature Genre Text of High School in Mataram City,West Nusa Tenggara .The problem in this research are : How is  the ability to produce  exposition text by students senior high school based on the structure of the exposition text. The approach used in this study is a qualitative and quantitative approach. Population Data  of this research are exposition text.The methode of data collection is done by listening to the method of proficiency involved.Data were analyzed qualitative and quantitative then presented through informal methods. The result of this study indicate that the ability of students  Senior High School of  Mataram city in producing exposition text is in the category of  underprivileged, that is equal to 57,50 under category of  sufficiently  capable score (67-78). The inability appear also qualitatively in lack of proper use of understanding of  based exposition text.